Prevalence of Scabies in Skin and VD OPD of DMCH - Ali, CM; Kamal, SMB; Ahmed, N; Sikdar, TK; Haque, AKMR; Parvez, MZ; Haque, ME; Rahman, MF (Bangladesh Medical Journal, 2011)
DOI: 10.3329/bmj.v39i2.7034 Bangladesh Medical Journal 2010, 39(2) pp.30-34